2015
DOI: 10.1021/acsami.5b01069
|View full text |Cite
|
Sign up to set email alerts
|

Killing Dental Pathogens Using Antibacterial Graphene Oxide

Abstract: Dental caries and periodontal diseases have a close relationship with microbes such as Streptococcus mutans, Porphyromonas gingivalis and Fusobacterium nucleatum. Graphene oxide (GO), as the derivative of graphene, plays an important role in many areas including biology and medicine. In particular, it has been known as a promising antimicrobial nanomaterial. In this study, we focused on the antimicrobial property of GO against dental pathogens. With the utilization of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
179
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(187 citation statements)
references
References 44 publications
6
179
2
Order By: Relevance
“…[42][43][44] In the study, GO-Ag coatings are produced on the Ti surface via an economical and simple method, which is electroplating and UV reduction. Although it is reported 45 that the antimicrobial effect of GO is prominent, it could promote the growth of bacteria, which is consistent with the results of Ruiz et al and Hui at al. 46, 47 Ruiz et al 46 showed that GO does not have antimicrobial ability.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…[42][43][44] In the study, GO-Ag coatings are produced on the Ti surface via an economical and simple method, which is electroplating and UV reduction. Although it is reported 45 that the antimicrobial effect of GO is prominent, it could promote the growth of bacteria, which is consistent with the results of Ruiz et al and Hui at al. 46, 47 Ruiz et al 46 showed that GO does not have antimicrobial ability.…”
supporting
confidence: 91%
“…Additionally, Mei et al 49 revealed that Ag is a superior antimicrobial agent, promotes fibroblasts and epithelial cells to proliferate and differentiate in vitro, and causes less inflammation in vivo. Also, He et al 45 indicates that the antimicrobial effect of GO nanosheets is prominent against P. gingivalis. There are five explanations, including damaging DNA of bacteria, interrupting cell signal transduction, 50 oxidative damage of reactive oxygen species, 51 intracellular contents leaked out 52 and dehydrogenase inactivation.…”
mentioning
confidence: 99%
“…Transmission electron microscopy images showed that the cell walls and membranes of bacteria lost their integrity, and the intracellular contents leaked out after they were treated by GO. Therefore, GO nanosheets would be an effective antibacterial material against dental pathogens, which has potential promising applications in contemporary dentistry [52].…”
Section: Graphenementioning
confidence: 99%
“…It is the first two-dimensional crystalline material ever produced. Owing to its unique properties of two-dimensional structure, high active surface area, mechanical resistance, conductivity, transparency and thermal resistance, graphene has characteristics on which thousands of researchers have been focusing their attention in the last decade via fundamental studies for future applications (Wolf, 2014, Russel et al, 2014He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%